Intervenções estruturantes na urbanização de assentamentos precários: o caso da Vila Nossa Senhora de Fátima - Eduardo Moutinho Ramalho Bittencourt (2014)
Slums and other forms of poor people's dwelling in Brazilian cities aren't an undesirable outcome of urban growth. Those informal seizures reflect urban spoliation and different paths to wealth accumulation in the production of cities. State, planning and urbanization are decisive portions of this project, by reinforcing the conditions that prevent those inhabitants from having access to the city. Slum upgrading (UAP, from the Portuguese acronym) appear today as the State's response in order to unwind the historical background of governmental neglect towards those settlements. This is the end result of a long process, in which social movements, academia, multilateral agencies such as ONU-Habitat, and local government officials took part. UAP has become consolidated public policy and has been intensely reproduced in all Brazilian cities. In the last 20 years, slum improvement in Belo Horizonte has converged towards the structural intervention model known as "Vila Viva" Program, which promotes extensive improvements in slums with the aim of ensure them the same conditions as the rest of the city. These actions have produced numerous social and spatial impacts in the slums where they have been attempted. This study follows the hypothesis that this model has not been successful, due to contradictions in discourse and practice regarding this kind of UAP. We analyze the models influencing its conception and contrast them with the reality of the "improved" slum, using data from interviews with the main stakeholders of urbanization as production of spaces (which are the dwellers and government officials) in Vila Nossa Senhora de Fátima (one of the intervention sites).